2002
DOI: 10.1262/jrd.48.281
|View full text |Cite
|
Sign up to set email alerts
|

Protamine-Derived Synthetic Peptide Enhances the Efficiency of Sperm-Mediated Gene Transfer Using Liposome-Peptide-DNA Complex.

Abstract: Sperm-mediated gene transfer (SMGT), which uses sperm cells as vectors for DNA delivery during fertilization, is one of the methods used to achieve transgenesis in animals as an alternative to pronuclear microinjection. Despite the convenience of SMGT, its application in producing transgenic animals, especially domestic animals, is still limited due to its low success rate. In this study, to increase the efficiency of SMGT, we tested liposome-peptide-DNA (LPD) complex, a new reagent known to stabilize transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…8 Similar results have also shown a lack of uptake of foreign DNA by rodent spermatozoa in the absence of lipid carriers. 14 The current study’s findings further confirm that liposomal carriers facilitate the movement of foreign genes across the cell membranes of host cells and incorporation into the host cell genome.…”
Section: Discussionsupporting
confidence: 75%
“…8 Similar results have also shown a lack of uptake of foreign DNA by rodent spermatozoa in the absence of lipid carriers. 14 The current study’s findings further confirm that liposomal carriers facilitate the movement of foreign genes across the cell membranes of host cells and incorporation into the host cell genome.…”
Section: Discussionsupporting
confidence: 75%
“…From this study, it was suggested that SMGT-AI can be successfully adapted for the generation of Tg livestock. Yonezawa et al [99] tested whether liposome-peptide (derived from human protamine)-DNA complex (LPD), a new reagent known to stabilize transfection in cultured cells, was useful to increase the efficiency of SMGT. They performed AI using rat epididymal sperm that had been incubated in a solution containing GFP expressing plasmid DNA and LPD complex.…”
Section: Historical Background Of Smgt-based Aimentioning
confidence: 99%
“…This process, termed sperm-mediated gene transfer (SMGT), provides a simple and straightforward method to produce transgenic animals. However, the SMGT protocol has been extended to many animal species, including mice [3] , [4] , rats [5] , rabbits [6] , and pigs [7] , [8] . It has also been a controversial issue in the past two decades as several other groups reported failure in repeat the original gene transfer protocol [9] .…”
Section: Introductionmentioning
confidence: 99%